1993
DOI: 10.3109/00016489309135784
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects on Hair Cells of Guinea Pig Cochlea Produced by Pneumolysin, the Thiol Activated Toxin ofStreptococcus pneumoniae

Abstract: The cytolytic toxin, pneumolysin, from the gram positive bacterium, Streptococcus pneumoniae, when perfused through the scala tympani of the guinea pig cochlea reduced the amplitude of both the compound action potential and the cochlear microphonic potential. When the surface of the organ of Corti was examined by scanning electron microscopy, both inner and outer hair cells and supporting cells were found to be damaged. Inner hair cells and outer hair cells of row 3 were the most susceptible to damage by pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 12 publications
3
34
1
Order By: Relevance
“…Use of adjunctive doxycycline also resulted in a moderate but significant decrease in the ABR thresholds of infected animals compared to the ABR thresholds of the animals that received only saline. This partial protection may reflect previous damage to the hair cells during the acute disease, probably caused by factors that adjunctive doxycycline could not attenuate, such as the release of bacterial pneumolysin in the perilymphatic and endolymphatic spaces (10,46). If this is the case, the withdrawal of neurotrophins normally produced by the hair cells might further aggravate neuron loss in the spiral ganglion (30).…”
Section: Discussionmentioning
confidence: 99%
“…Use of adjunctive doxycycline also resulted in a moderate but significant decrease in the ABR thresholds of infected animals compared to the ABR thresholds of the animals that received only saline. This partial protection may reflect previous damage to the hair cells during the acute disease, probably caused by factors that adjunctive doxycycline could not attenuate, such as the release of bacterial pneumolysin in the perilymphatic and endolymphatic spaces (10,46). If this is the case, the withdrawal of neurotrophins normally produced by the hair cells might further aggravate neuron loss in the spiral ganglion (30).…”
Section: Discussionmentioning
confidence: 99%
“…In pneumococcal meningitis, pneumolysin causes the death of cochlear cells and subsequent hearing loss (12,40). Independently of the inflammatory response, pneumolysin also mediates neuronal loss in the dentate gyrus, where it is colocalized with neurons undergoing apoptosis (4).…”
mentioning
confidence: 99%
“…This work and that of others (5,24) has led us to believe that blocking the toxic effects of pneumolysin may be advantageous, and the aim of the present study was to determine the ability of antipneumolysin antibodies to reduce damage to the ependymal layer. The rapid release of pneumolysin on antibiotic-induced bacterial lysis (23) is thought to contribute to toxic shock and local tissue damage and may partially be responsible for causing deafness (7). Recently we have shown that pneumococci and pneumolysin cause rapid ependymal ciliary stasis in ependymal brain slices and cultured primary ependymal cells (12), an effect that is mirrored in experimental meningitis in rats (11).…”
mentioning
confidence: 95%